Spin distribution measurements in 16O+159Tb system: incomplete fusion reactions. (9th April 2015) - Sharma, Vijay R; Yadav, Abhishek; Singh, Pushpendra P; Bala, Indu; Singh, Devendra P; Gupta, Sunita; Sharma, M K; Kumar, R; Muralithar, S; Singh, R P; Singh, B P; Bhowmik, R K; et al.
Abstract: The spin distributions of complete and incomplete fusion residues populated in the 16 O+ 159 Tb system have been measured using the particle- γ coincidence technique to investigate the role of high angular momentum values in the production of direct- α -emitting channels. Spin distributions of various αxn channels are measured at ELab ≈ 6.2 MeV A −1 . Entirely different de-excitation patterns are observed in direct- α -emitting channels and fusion-evaporation channels. The fusion-evaporation channels are found to be strongly fed over a broad spin range. While narrow range feeding for only high-spin states was observed in the case of direct- α -emitting channels. To have a better insight into the associated angular momenta values in different reaction channels, the present data are compared with similar data from [1, 2 ]. The mean driving angular momenta involved in the production of direct- α -emitting channels are found to be higher than those involved in the production of fusion-evaporation channels.